2023
DOI: 10.1007/s11250-023-03457-y
|View full text |Cite
|
Sign up to set email alerts
|

Udder, teat, and milk vein measurements of Indian dromedary camel and its relationship with milkability traits

Abstract: The economic viability of the camel in the current scenario can be ensured by improving its dairy potential. The study on the udder and teat characteristics of dromedary and its relationship with milk yield and milkability can be of great value in establishing camel as a dairy animal. The present study was conducted on 45 lactating she-camels of four Indian camel breeds viz. Bikaneri, Jaisalmeri,Kachchhi and Mewari stationed at ICAR-NRCC Bikaner, Rajasthan (India). Various udder and teat morphology, milk yield… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Differences between animals of different parities could be related to a changing teat anatomy with advancing parity [17,27,30,57,58]. Milking characteristics varied according to the stage of lactation due to changes in milk yield with advancing lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between animals of different parities could be related to a changing teat anatomy with advancing parity [17,27,30,57,58]. Milking characteristics varied according to the stage of lactation due to changes in milk yield with advancing lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Because camels do not have gland cisterns for storage, milk production is a reflex secretion ( 42 ). Previous studies have demonstrated that milkability traits can be assessed using udder and teat morphological traits of camels, contributing to the selection of high-producing camels ( 43 ). Camel teats have a double ductal anatomy with a promising prophylactic effect against mastitis-causing pathogens ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar guidelines for linear score evaluation are also utilized by other organizations involved in the dairy cattle industry (Stamschror et al, 2000;Mwacharo et al, 2006;Anonymous, 2022). The udder numerical morphological values mentioned in this article have been obtained from various publications focusing on the udders of dairy camels (Eisa and Hassabo, 2009;Ayadi et al, 2016;Musaad et al, 2017;Kumar et al, 2023). The statistical analysis of the relevance of these values to milk production is available in those publications.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, it is also important to note that the rear quarters of a camel produce more milk than the front quarters (Eisa & Hassabo, 2009;Musaad et al, 2017;Kumar et al, 2023); therefore, rear-quarters asymmetry, that is, in which the rear quarters are larger than the front quarters, should not be considered a fault. Another factor to consider when assessing a camel's milking capacity is the size and development of the milk vein or subcutaneous abdominal vein as there is a relationship between a large diameter of the milk vein and abundant milk production (Eisa et al, 2010;Braun and Forster, 2012;Gracner et al, 2015;Berger et al, 2016;Kumar et al, 2023). In lactating camels, a large and long milk vein is considered a positive attribute (Figure 12A), whereas a poorly developed or barely visible milk vein should be viewed as a negative attribute (Figure 12B).…”
Section: Udder Quarter Assessmentmentioning
confidence: 99%